New constraints from Central Chile on the origins of enriched continental compositions in thick-crusted arc magmas. (15th December 2019) - Wieser, Penny E.; Turner, Stephen J.; Mather, Tamsin A.; Pyle, David M.; Savov, Ivan P.; Orozco, Gabriel
Abstract: Magmas from continental arcs built on thick crust have elevated incompatible element abundances and "enriched" radiogenic isotope ratios compared to magmas erupted in island and continental arcs overlying thinner crust. The relative influence of the slab, mantle, and upper plate on this variability is heavily debated. The Andean Southern Volcanic Zone (SVZ; 33–46°S) is an ideal setting to investigate the production of enriched continental arc compositions, because both crustal thickness and magma chemistry vary coherently along strike. However, the scarcity of primitive magmas in the thick-crusted northern SVZ has hindered previous regional studies. To better address the origin of enriched continental compositions, we investigate the geochemistry (major and trace element abundances, 87 Sr/ 86 Sr and 143 Nd/ 144 Nd ratios) of new mafic samples from Don Casimiro and Maipo volcanoes within the Diamante-Maipo Caldera Complex of the northern SVZ. While evolved Diamante-Maipo samples show evidence for crustal assimilation, the trace element and isotopic enrichment of the most mafic samples cannot result from crustal processing, as no known regional or global basement lithologies are enriched in all of the necessary incompatible trace elements. Subduction erosion models similarly fail to account for the enriched isotopic and trace element signature of these samples. Instead, we suggest that the enrichment of northern SVZ magmas is derived from an enriched ambient mantle component (similar to EM1-type ocean island basalts), superimposed on a northward decline in melt extent. A substantial, but nearly uniform contribution of melts from subducting sediment and altered oceanic crust are required at all latitudes. The EM1-like enrichment may arise from recycling of metasomatized subcontinental lithospheric mantle (M-SCLM), as the isotopic trajectory of primitive rear-arc monogenetic cones trend towards the compositions of SCLM melts sampled across South America. Isotopic data from spatially distributed rear-arc centres demonstrate that the arc-parallel variations in the degree of EM1-type enrichment observed in arc-front samples are also present up to 600 km behind the trench in the rear-arc. Rear-arc trace element systematics require significant but variable quantities of slab melts to be transported to the mantle wedge at these large trench distances. Overall, we show that a unified model incorporating variable mantle enrichment, slab additions, and melt extents can account for along and across-arc trends within the SVZ. The recognition that mantle enrichment plays a key role in the production of enriched continental compositions in the SVZ has important implications for our understanding of the chemical evolution of the Earth. If ambient mantle enrichment is not taken into account, petrogenetic models of evolved lavas may overestimate the role of crustal assimilation, which, in turn, may lead models of continental crust growth to overestimate the amount of continental material that has been recycled back into the mantle.